"Efectividad del programa educativo: Mejorando mis saberes acerca de las loncheras escolares, en el nivel de conocimientos, de padres de niños preescolares. La Esperanza, 2009" - Abanto Abanto, Jenny Lisset (2009)
The present investigation, of type preexperimental there was realized in the Educational Institution Fátima N's Virgin Initial º 1682, during the months of Julio - August, 2009, with the purpose of determining the “Efficiency of the Educational Program: Improving my Saberes it brings over of school Loncheras, in the Level of Knowledge, of parents of pre-school children”. The sample was constituted by 30 family parents who fulfilled the criteria of choice mentioned in the investigation. For the compilation of information the instrument was in use: Scale of Knowledge on Loncheras (ECL), being the obtained information tried and analyzed by means of: the statistical test "t" of Student for related samples; the results are presented in tables of simple, double entry and graphs. With the obtained results we come to the following conclusions: - 76.6 per cent of parents of pre-school they were presenting an average level of knowledge, before the application of the Educational Program. - 96. 6 per cent of parents of pre-school they presented a high knowledge, after the application of the Educational Program. - The Educational Program was effective on having increased the level of knowledge in parents of pre-school in significant form.